CHEMICAL BIO-COMPOUNDS AND FUNCTIONAL PROPERTIES OF RAW AND PROCESSED CUTTLEFISH, SEPIA OFFICINALIS (MOLLUSCA: CEPHALOPODA) - Aderonke O. LAWAL-ARE (Stefan cel Mare University of Suceava, 2018)
Cuttlefish is one of the most economically important cephalopods with rich taste and few inedible parts. The study was aimed at evaluating the nutrient, non-nutrients, free fatty acid and cholesterol compositions and functional properties of raw and processed Sepia officinalis using standard methods. Moisture and raw protein in raw sample of the cuttlefish were significantly higher (𝑃< 0.05) than in processed samples. Raw fat showed significant differences with fried sample having highest value (22.39±0.54 %) to raw (16.24±0.10 %) and boiled samples (4.09±1.42 %). Raw sample contained more ash with highest mg/100g levels of calcium, phosphorus, magnesium, iron and manganese. Processed cuttlefish registered significant reduction in levels of trypsin inhibitor, phytate and oxalate compared to the raw. Raw protein of fried cuttlefish exhibited positive relationships with all the non-nutritionalfactors while total ash only showed positive relationships with phytate (𝑟 = 0.998) and trypsin inhibitor (𝑟 = 0.999). Cholesterol content of raw cuttlefish was of 0.923±0.02 mg/100g being reducedby boiling (0.711±0.02 mg/100g) and increased by frying (1.037±0.02 mg/100g). A significantly high percentage of oleic was observed in fried cuttlefish (4.47±0.10) while boiled sample had the lowest value (1.4±0.05). The results showed significantly high percentage of water and oil absorbing capacities for raw cuttlefish while foam and emulsion stabilities were higher in the boiled sample. By frying, the highest foam and emulsion capacities of 8.8 and 4.4% respectively were obtained. The study suggests that Sepia officinalis will be highly desirable for preparing comminuted sausage products due to its good functional and nutritional properties.